Integration of Sustainability into the operation of businesses through Human Resource Management Education - Attila Pongrácz; Szabolcs Rákosi (Chemical Engineering Transactions, 2023)
This research focuses on a hardly studied dimension of Sustainability, on its aspects of Human Resource Management (HRM). The examination of the topic is justified by the fact that the emergence of Sustainable Human Resources Management (SHRM) as one of today's modern, innovative HR approaches has not yet been examined in Hungary. Thus, the research fills a gap. The study aims to investigate how and to what extent Sustainability is implemented in the HRM practices of businesses of different sizes in the Northwest-Hungarian Economic Development Zone. The questionnaire survey forming the basis of this study was carried out by interviewing managers and HR professionals of the companies. The results indicate that Sustainability appears in extremely diverse ways and degrees in the examined organizations. The vast majority of them still consider Sustainability to be a primarily environmental issue. During their operations, the companies highlight the economic and environmental aspects of Sustainability and, despite the labor shortage, do not place a significant emphasis on Sustainability in the areas of Staffing, Compensation Management, and Staff Development. As a result of this research, Széchenyi István University ensures, through the development of HR training, that future professionals can develop and operate the model of SHRM in practice by taking into account new aspects and applying a complex approach. The results of the study will not only provide new value for the academic sphere but can also contribute to more efficient and fair operation of businesses.